Strategi Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan (Studi Kasus Madrasah Aliyah Bahrul Ulum Tajinan Kabupaten Malang) - Hasyim Mujadi (STAI Ma'had Aly Al-Hikam Malang, 2021)
Madrasah Aliyah Bahrul Ulum Tajinan Malang is one of the educational institutions under the auspices of the Bahrul Ulum Tajinan Islamic Boarding School Foundation, Malang. This Madrasah is very thick with its religious atmosphere, because it stands in a pesantren environment. This madrasah has good quality education seen for the several programs it has, namely 8 excellent programs., as well as standart operational for learning noble character and habituation of noble character. In addition, this madrasah also has several prominent programs, they are: 1) discipline, 2) dhuha prayer activities and reading yaaseen, 3) complete facilities and infrastructure. Therefore, the author wants to examine how the principal’s strategy in improving the quality of education at Madrasah Aliyah Bahrul Ulum.This research was conducted in Madrasah Aliyah Bahrul Ulum Tajinan Malang. Research data obtained through observation, interviews, and documentation. To check the validity of the data using triangulation of sources and methods. Data analysis uses interaction model analysis techniques with three stages, namely data reduction, data presentation, and drawing conclusion.The results of the study, the principla’s strategy in improving the quality of education in Madrasah Aliyah Bahrul Ulum Tajinan Malang are namely, 1) improving the quality of educators and education, 2) fostering the discipline of teachers and students, 3) increasing the effectiveness of learning, 4) improving madrasah facilities and infrastructure, 5) improving the quality of learning and stucent achievement, 6) evaluation of teaching and learning process, and 7) promoting madrasah.